Tachinid flies of the Ussuri area (Diptera: Tachinidae). Contributions to the knowledge of East Palaearctic insects (5). - Ziegler, Joachim; Shima, Hiroshi (Contributions to Entomology = Beiträge zur Entomologie, 1996)
Tachinid flies from the Russian Far East were studied: 448 species are for the first time compiled for the Russian Far East, of which 362 species are recorded from the Ussuri area; 32 species are recorded from Russia for the first time; 53 species are new for the Russian Far East and 71 species are reported for Ussuria for the first time. In addition to the faunistic data, brief ecological, morphological and zoogeographical remarks are given. A new synonym is established: Anameriana albomicans Zimin, 1960 syn. nov. of Bothria japonica Mesnil, 1957. Redescriptions are given for Ctenophorinia adiscalis Mesnil, 1963, Ctenophorinia grisea Mesnil, 1967 and Erythrocera longicornis (Brauer & Bergenstamm, 1891). The following seven species are described as new to science: Ctenophorinia christianae sp. n., Ctenophorinia frontalis sp. n., Medina confinis sp. n., Oswaldia intermedia sp. n., Paratryphera grandis sp. n., Campylocheta similis sp. n. and Hemyda hertingi sp. n. Nomenclatural Acts similis Ziegler & Shima, 1996 (Campylocheta), spec. n. christianae Ziegler & Shima, 1996 (Ctenophorinia), spec. n. frontalis Ziegler & Shima, 1996 (Ctenophorinia), spec. n. hertingi Ziegler & Shima, 1996 (Hemyda), spec. n. confinis Ziegler & Shima, 1996 (Medina), spec. n. intermedia Ziegler & Shima, 1996 (Oswaldia), spec. n. grandis Ziegler & Shima, 1996 (Paratryphera), spec. n.